Hubungan Nilai Mata Kuliah Aljabar Linier Sebagai Prasarat Terhadap Nilai Mata Kuliah Teknik Riset Operasional - Hasanah, Huswatun; Yanuar, Melinda; Abadi, Ma'ulfi Kharis (Jurnal Ilmu Pendidikan Muhammadiyah Kramat Jati, 2024)
Linear Algebra and Operational Research Techniques are two very important courses in the disciplines of mathematics and engineering. A strong understanding of Linear Algebra is considered a very important prerequisite for being able to master and apply various methods in Operational Research Techniques. Therefore, the existence of a significant relationship between Linear Algebra scores and Operational Research Technique scores is interesting to study further, especially in the context of identifying the extent to which mastery of Linear Algebra influences the understanding and application of concepts in Operational Research. The aim of this research is to see the relationship between students' Linear Algebra learning outcomes and Operations Research Engineering learning outcomes. The research method is correlational research using descriptive analysis with the help of SPSS 27, data normality testing using the Shapiro-Wilk test, Pearson correlation test, whereas if one of the data comes from data that is not normally distributed, then the statistical test carried out is a non-parametric statistical test. Spearman's rho. Then, proceed with the coefficient of determination test to see what percentage influence the results of learning Linear Algebra have on the results of learning Operational Research Engineering students. The conclusion from the research conducted is that there is a relationship between learning outcomes for Linear Algebra and learning outcomes for Operational Research Techniques which is in the strong category (0.765). The results of the subsequent analysis concluded that 59.80% of students' results of learning Operational Research Techniques in Linear Programming material were influenced by the results of Linear Algebra in Systems of Linear Equations material.